'What I cannot create, I do not understand': functionally validated synergism of metabolic and target site insecticide resistance. Issue 1927 (27th May 2020) - Samantsidis, George-Rafael; Panteleri, Rafaela; Denecke, Shane; Kounadi, Stella; Christou, Iason; Nauen, Ralf; Douris, Vassilis; Vontas, John
Abstract : The putative synergistic action of target-site mutations and enhanced detoxification in pyrethroid resistance in insects has been hypothesized as a major evolutionary mechanism responsible for dramatic consequences in malaria incidence and crop production. Combining genetic transformation and CRISPR/Cas9 genome modification, we generated transgenic Drosophila lines expressing pyrethroid metabolizing P450 enzymes in a genetic background along with engineered mutations in the voltage-gated sodium channel ( para ) known to confer target-site resistance. Genotypes expressing the yellow fever mosquito Aedes aegypti Cyp9J28 while also bearing the para V1016G mutation displayed substantially greater resistance ratio (RR) against deltamethrin than the product of each individual mechanism (RRcombined : 19.85 > RRCyp9J28 : 1.77 × RRV1016G : 3.00). Genotypes expressing Brassicogethes aeneus pollen beetle Cyp6BQ23 and also bearing the para L1014F ( kdr ) mutation, displayed an almost multiplicative RR (RRcombined : 75.19 ≥ RRCyp6BQ23 : 5.74 × RRL1014F : 12.74). Reduced pyrethroid affinity at the target site, delaying saturation while simultaneously extending the duration of P450-driven detoxification, is proposed as a possible underlying mechanism. Combinations of target site and P450 resistance loci might be unfavourable in field populations in the absence of insecticide selection, as they exert some fitness disadvantage in development time and fecundity. These are major considerations from the insecticide resistance management viewpoint in both public health and agriculture.